Use of GIS to delineate site-specific management zone for precision agriculture (2017)
Soil heterogeneity is one of the several factors that explain within-field variations in crop yielding. To overcome this problem, experiment was conducted within the University of Ibadan to identify the zones with similar soil properties that can be managed uniformly to optimize crop yield. A total of 62 soil samples were collected from 6.5 ha of farmland based on the differences in slope, soil moisture regime, land management and cropping pattern. The spatial distributions of soil properties were mapped out using Inverse Distance Weighing (IDW) interpolation technique and the results were subsequently reclassified into different soil management categories. The results showed that the farmland consists of four classes of total nitrogen (N), phosphorus (P) and soil bulk density (SBD); three classes of carbon © and oxygen (Ө); two classes of soil pH; one class of soil texture. Each of the soil management maps was subsequently overlaid on each other to produce four specific site management units (SSMU) for vegetable cultivation. The four SSMU consisted of highly suitable unit occupying 0.143 ha, marginally suitable unit occupying 0.971 ha, moderately suitable unit occupying 0.517 ha and unsuitable unit occupying 4.9 ha of land. The SSMU will alleviate problems of reduced yield due to over or under applications of agrochemicals.